2018
DOI: 10.1002/mrd.23044
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ICSI outcome by combining non‐invasive indicators: Early time‐lapse morphokinetics and apoptosis in associated cumulus cells among women with the polycystic ovarian syndrome

Abstract: Cumulus cells features and embryo developmental events can be considered as noninvasive indicators for embryo selection and clinical outcomes. A combination of time-lapse morphokinetic parameters and cumulus cell apoptosis in women with polycystic ovarian syndrome (PCOS) was evaluated for predicting pregnancy outcome. We assessed a total of 547 embryos from 100 intracytoplasmic sperm injection (ICSI) cycles. Time-lapse records were interpreted in time to pronuclear fading (tPNf), time to 2 to 8 cells (t2-t8), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It can be considered as a predictor of pregnancy and live birth, and the percentage of apoptotic CCs is an independent prognostic factor for these outcomes. For every 1% increase in CC apoptosis, the clinical pregnancy and live birth rates will decrease by 11–12% [ 102 ].…”
Section: Cumulus Cell Biomarkers and Pregnancy Outcomementioning
confidence: 99%
“…It can be considered as a predictor of pregnancy and live birth, and the percentage of apoptotic CCs is an independent prognostic factor for these outcomes. For every 1% increase in CC apoptosis, the clinical pregnancy and live birth rates will decrease by 11–12% [ 102 ].…”
Section: Cumulus Cell Biomarkers and Pregnancy Outcomementioning
confidence: 99%
“…One study demonstrated that for every one percent increment in CC apoptosis, the clinical pregnancy and live birth rates will be decreased by 11-12% (73). There are many external as well as internal stimuli that promote this alteration, such as endocrine abnormalities, high levels of stress oxidative products, hyperandrogenic state, and imbalance of the LH/FSH ratio.…”
Section: Genes Related To Cumulus Expansion and Apoptosismentioning
confidence: 99%
“…68,83 Furthermore, the level of GC apoptosis showed a negative correlation with pregnancy and live birth in PCOS patients, as every 1% elevation in the abundance of apoptotic GCs was associated with an 11%-12% decrease in the likelihood of successful pregnancy and live birth. 84…”
Section: Experimental Setting Species Pdcd4 Expression Cell Cycle Pro...mentioning
confidence: 99%